The Struggle Of The Tabanan Women As “Sentana Rajeg” In The Patriarchal Culture Domination In Bali - Cupu Tyasningrum, Ayu Agung; Susanti, Emy; Sutinah, Sutinah (Opción, 2019)
This is because the Balinese follow the patrilineal system which follows the father’s lineage, which is called kapurusa. The kaprusa system places men at the top and they become the heirs of the family. The kaprusa system also places men as purusa and women as predana. Not all families have sons and some only have daughters. To overcome this problem, the family will raise their daughters to become sentana rajeg to overcome the family’s difficulties of not having putung because they do not have sons. They seek to give equal rights to their daughters, which are the rights that would normally be obtained by boys. To strengthen the status of a sentana rajeg, nyentana marriage must be done. This is where men are married and live in women’s homes. The appointment of the rajent sentana has been carried out in the Tabanan community through nyentana marriages. The marriage of nyentana as a form of matrilineal mar- riage was broken by the domination of patriarchal culture. The purpose of this writing is to describe the process of appointing women to be sentana rajeg so then women have the same position as men in a marriage. The method used in this research was qualitative using primary data from the results of the field research and the interviews related to it. The location of this research was in Tabanan Regency using Jacques Deridda’s deconstruction theory.